Immune Regulatory 1 Cells: A Novel and Potent Subset of Human T Regulatory Cells - Krause, Nicolas; Mengwasser, Jörg; Phithak, Elpida; Beato, Francisca; Appis, Marc; Milford, Edgar Louis; Pratschke, Johan; Sauer, Igor; Kuehl, Anja; Vogel, Arndt; Goodyear, Michael; Hammerich, Linda; et al. (Frontiers in Immunology, 2022)
A subset of T regulatory cells (Tregs), identified by TIRC7 (T cell immune response cDNA 7) expression is designated as Immune Regulatory 1 Cells (IR1 cells). TIRC7 is an immune checkpoint inhibitor, co-localized with the T- cell receptor, HLA-DR and CTLA-4 during T-cell activation, which delivers regulatory signals via binding to its ligand, HLA-DR α2 domain. IR1 cells express FOXP3, and multiple other markers associated with immune suppression. They constitute as much as 10% of Tregs. IR1 cells strongly inhibit proliferation in mixed lymphocyte reactions, where they express high levels of IL-10. Ex vivo expansion of Tregs over 2 weeks in the presence of an agonist TIRC7 antibody disproportionately expands the IR1 Treg subset, while maintaining high expression of suppressive markers including CD39, IL-10, LAP and GARP. Ex vivo expanded IR1 cells are a potent, homogeneous, stable set of suppressor Tregs with the potential to modulate immune dysregulation. The characteristics of IR1 cells suggest a therapeutic advantage over polyclonal Tregs for therapeutic interventions. Early restoration of immune homeostasis using IR1 cells has the potential to fundamentally alter the natural history of conditions characterized by abnormalities in the T regulatory cell compartment.